Pembelajaran Berdiferensiasi pada Kurikulum Merdeka Tingkat Pendidikan Anak Usia Dini di Kecamatan Kaur - Ayuni, Despa; Julianto, Alfin; Handayani, Yulita; Nasution, Siyyella Tika; Widodo, Arip; Oktari, Rici; Putri, Ridha Fadila (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Differentiated learning is learning in which a quality curriculum is important in learning, so curriculum innovations are often made from time to time. There are still many PAUD teachers who are still confused due to new things in implementing differentiated learning in the current independent curriculum. The seminar on the implementation of differentiated learning in the independent curriculum at the early childhood education level in Kaur District is the theme of this community service activity. Aims to provide understanding and knowledge of PAUD educators in implementing differentiated learning in the curriculum. The results of the service are that the participants gave a positive response, consistently followed the activities from start to finish, did the assignments given in a timely manner so as to increase the participants' insight to implement differentiated learning in their respective institutions. Differentiated learning is formed through the way of thinking of teachers who consider that every child can grow and develop optimally according to their respective capacities.